SOCIAL-ECONOMIC ROLE OF SMALL BUSINESS IN THE PROGRESSIVE DEVELOPMENT OF RUSSIA - L. G. Rudenko (Russian Journal of Economics and Law, 2016)
Objective: to assess the socio-economic significance of small business in the services sector of national economy and to develop effective tools of its infrastructural support, basing on the characteristics of the services sector.Methods: systematic approach was applied to identify the characteristics of small businesses in the services sector; methods of comparative and statistical analysis were used to assess the contribution of small business in service sector to the economic development of the country; methods of analysis and synthesis revealed problems of development of small business in service sector; program and target method was used to develop infrastructural tools to support small businesses.Results: social and economic characteristics of small business in services were determined; the contribution of small business in service sector into the economic progress of the country was assessed; the problems and peculiarities of development of small entrepreneurship in services were identified and examined. Basing on the analysis of problems of small business growth and its role in the progressive development of the economy, the necessity of state support is proved, and the effective tools of infrastructure support for small businesses are determined, basing on the characteristics of the service sector.Scientific novelty: the characteristics of small business in services are identified and grouped by economic and social principle; the growing contribution of the small business in service sector to the Russian economy is proved, and its backlog from the developed economies is confirmed; problems hindering the development of small business are identified. Basing on the problems, effective tools for small business support are developed and offered.Practical significance: the main provisions and conclusions of the research can be used in scientific activity to study the development and infrastructural support of small business in services sectors; they can be used by public authorities to develop a strategy of small business development and programs of services development, as well as forms, methods and tools of infrastructural support of small business.